THE USE OF LIVE FOOD IN REARING OF THE LARVAE OF GRASS CARP CTENOPHARYGODON IDELLA - AL- NOOR, S.S.; Ali, M.H.; GAHZI, A. H. (Iraqi Journal of Aquaculture, 2022)
The larvae of grass carp Ctenophargodon idella were fed on three types of live food Brachionus calyciflorus, Artemia sp. and Daphnia magna. The study showed that live food is very important to achieve high growth and survival of fish larvae. The average weights of C. idella fed on B. calyciflorus were 118.12+3.0 mg / larvae and 29.48+0.8 mm / larvae respectively, and in case of Artemia sp. The rates were 103.13+1.5 mg/ larvae and 25.34+1.4 mm / larvae, while in the mixed food the rate were 122.80 + 1.8 mg / larvae and 30.08 + 1.1mm /larvae .The survival rate was better on B. calyciflorus treatment as it was 98.6 % ,while it was 98 % and 97% in case of mixed food and Artemia sp. Respectively .